Effect of Dietary Salt and Zinc Level on Growth Performance and Fecal Dry Matter of Nursery Pigs - Ethan B. Stas; Mike D. Tokach; Jason C. Woodworth; Joel M DeRouchey; Robert D. Goodband; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 360 pigs (Line 600 × 241, DNA; initially 12.6 ± 0.5 lb) were used to determine the effect of feeding different levels of dietary Na alone or in combination with pharmacological levels of Zn on growth performance and fecal dry matter of nursery pigs. At weaning, pigs were randomly allotted to pens (6 pigs per pen) and fed a common diet for 7 days. On d 7 after weaning (d 0 of the trial), pigs were assigned to 1 of 6 dietary treatments with 10 replications per treatment. Dietary treatments were arranged in a 2 × 3 factorial with main effects of added Zn (0 or 2,000 ppm Zn from ZnO) and Na (0.13, 0.24, or 0.35% from salt). All diets contained 110 ppm of Zn from ZnO from the trace mineral premix. Following a 14-d experimental period, pigs were fed a common phase 3 diet for 21 days. From d 0 to 14, increasing Na increased (linear,P<0.05) ADG, ADFI, and BW. The addition of ZnO in the diet also increased (P<0.001) ADG, ADFI, and BW. An interaction (linear,P= 0.027) was observed where increasing Na up to 0.35% improved F/G from d 0 to 14 only when pharmacological levels of Zn were fed. Within the interaction, pigs fed diets without ZnO showed a response (quadratic,P= 0.027) in F/G as Na increased. When Na was increased from 0.13 to 0.24% F/G improved, but when Na was further increased to 0.35% F/G worsened. When 2,000 ppm of Zn was added, F/G improved (linear,P= 0.003) as Na increased. From d 14 to 35 and overall, an interaction was observed (linear,P<0.05) for F/G. Within the interaction, pigs fed diets without ZnO showed a linear increase in F/G as Na level increased (linear,P≤ 0.011). On d 7, fecal dry matter decreased and then subsequently increased (quadratic,P= 0.026) with increasing Na. Unexpectedly, pigs fed added Zn had decreased (P= 0.008) fecal dry matter on d 14. In summary, increasing dietary Na and the addition of pharmacological levels of Zn independently improved daily gain and feed intake in nursery pigs, but an improvement in F/G from increasing Na was only observed when pharmacological ZnO was also present.
Keywords: nursery pig; salt; zinc; growth; fecal dry matter